A principal component analysis of corporate dispositions for sustainable building construction in South Africa - Emere, Chijioke Emmanuel; Aigbavboa, Clinton Ohis; Oguntona, Olusegun Aanuoluwapo; Ogunbayo, Babatunde Fatai (Frontiers in Built Environment, 2024)
Corporate dispositions have been associated with implementing sustainable building construction (SBC). Prior studies have underscored the need for institutions to adopt sustainable development concepts as an integral part of their operations. Nonetheless, there remains ambiguity about the characteristics essential for enabling SBC, particularly for construction companies. Consequently, this study explored the corporate dispositions influencing SBC implementation in South Africa. The respondents included built environment professionals in the Gauteng province of South Africa. Descriptive and principal component analyses were used to determine the essential characteristics or features. The study found that top management support, competency, availability of finance for the project operation, good project management culture, stakeholders’ involvement and commitment, and commitment to innovative construction are the most critical corporate disposition features for SBC implementation. These formed a principal cluster called corporate capability and commitment. The insight from the critical corporate dispositions analysis is anticipated to trigger improvement initiatives and mitigate unsustainable practices and the unaffordability of smart houses in the South African construction industry. The findings suggest that mobilising competent human and financial resources for project operation among construction firms will support the adoption of modern building techniques and the erection of smart houses. Similarly, competitive advantage and committed involvement of the relevant stakeholders, including government and community, can lead to subsidy, alignment of local needs and aspirations, and reducing the high price of erecting sustainable/smart buildings and rental costs.